2021
DOI: 10.1155/2021/9623571
|View full text |Cite
|
Sign up to set email alerts
|

Plasma D-Dimer Level Correlates with Age, Metastasis, Recurrence, Tumor-Node-Metastasis Classification (TNM), and Treatment of Non-Small-Cell Lung Cancer (NSCLC) Patients

Abstract: Objective. This study is aimed at teasing out the correlation of plasma D-dimer (D-D) levels to age, metastasis, TNM stage (tumor-node-metastasis classification), and treatment in non-small-cell lung cancer (NSCLC) patients of different ages, to facilitate early diagnosis of hypercoagulable state, choose appropriate treatment, and use appropriate anticoagulants. Hence, thrombosis and complications caused by excessive anticoagulants can be prevented; thrombus or disseminated intravascular coagulation (DIC) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…On this basis, the activation of a large number of inflammatory factors and chemokines caused by COPD enhanced the accessibility of lung cancer. At the same time, key transcription factors (such as nuclear factor- κ B, transcriptional signal transducers, and activators) involved in inflammatory response promoted rapid proliferation of tumor cells and tumor angiogenesis and thus activated epithelial-mesenchymal cell transformation, leading to tumor invasion and recurrence of NSCLC [ 15 ]. D-dimer was the end product of fibrinolytic degradation catalyzed by a fibrinolytic enzyme, which could reflect the synthesis status of fibrinolytic enzyme and thrombin in the body, and the increase of its level indicated the existence of hypercoagulability and secondary fibrinolytic hyperactivity in the body [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On this basis, the activation of a large number of inflammatory factors and chemokines caused by COPD enhanced the accessibility of lung cancer. At the same time, key transcription factors (such as nuclear factor- κ B, transcriptional signal transducers, and activators) involved in inflammatory response promoted rapid proliferation of tumor cells and tumor angiogenesis and thus activated epithelial-mesenchymal cell transformation, leading to tumor invasion and recurrence of NSCLC [ 15 ]. D-dimer was the end product of fibrinolytic degradation catalyzed by a fibrinolytic enzyme, which could reflect the synthesis status of fibrinolytic enzyme and thrombin in the body, and the increase of its level indicated the existence of hypercoagulability and secondary fibrinolytic hyperactivity in the body [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, key transcription factors (such as nuclear factor- κ B, transcriptional signal transducers, and activators) involved in inflammatory response promoted rapid proliferation of tumor cells and tumor angiogenesis and thus activated epithelial-mesenchymal cell transformation, leading to tumor invasion and recurrence of NSCLC [ 15 ]. D-dimer was the end product of fibrinolytic degradation catalyzed by a fibrinolytic enzyme, which could reflect the synthesis status of fibrinolytic enzyme and thrombin in the body, and the increase of its level indicated the existence of hypercoagulability and secondary fibrinolytic hyperactivity in the body [ 15 ]. The increase of plasma D-dimer after surgery suggested that the patient's coagulation and fibrinolysis system were dysfunctional, and abnormal coagulation could induce tumor recurrence [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, age and tumour infiltration grade were found to have a considerable impact on the survival of NSCLC patients. Guo et al (34) showed that plasma-related pulmonary artery embolism levels in NSCLC patients increased significantly with increasing age, and that the prognostic hypercoagulable status of NSCLC patients was related to patients' age, tumour infiltration grade and metastasis, and their postoperative treatment needed to take these factors into account. In addition, gender and ethnicity are important prognostic factors for patients with NSCLC, and gender is a strong prognostic factor when assessing the survival of patients with non-small cell lung cancer (35-37).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated plasma D-dimer levels are associated with poor prognosis in CRC [10] . Emerging evidence also suggested that plasma D-dimer levels were progressively increased in healthy people, nonmetastatic non-small cell lung cancer (NSCLC) patients, and patients with metastatic NSCLC [11] . Tumor cells promote the hypercoagulable state by secreting tissue factors and procoagulant substances, and interact with platelets to form microthrombus and promote hematogenous metastasis.…”
Section: Introductionmentioning
confidence: 99%